Murder on Washington Square - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Gaslight mystery., 2002)
When mild-mannered banker Nelson Ellsworth is accused of murdering his pregnant mistress, it will take the skills of both Sarah Brandt and Detective Frank Malloy to uncover the truth.